2017
DOI: 10.1088/1741-4326/aa86cf
|View full text |Cite
|
Sign up to set email alerts
|

Thermal desorption spectroscopy of high fluence irradiated ultrafine and nanocrystalline tungsten: helium trapping and desorption correlated with morphology

Abstract: Microstructural changes due to displacement damage and helium desorption are two phenomena that occur in tungsten plasma facing materials in fusion reactors. Nanocrystalline metals are being investigated as radiation tolerant materials that can mitigate these microstructural changes and better trap helium along their grain boundaries. Here, we investigate the performance of three tungsten grades (nanocrystalline, ultrafine and ITER grade tungsten), exposed to a high fluence of 4 keV helium at both RT and 773 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The retention of hydrogen isotopes in W is mainly affected by trap sites, such as dislocations, grain boundaries, vacancies and microvoids in the matrix material [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The retention of hydrogen isotopes in W is mainly affected by trap sites, such as dislocations, grain boundaries, vacancies and microvoids in the matrix material [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are affected by helium ion channeling, which occurs preferentially for certain crystalline orientations [1][2][3]. The channeling of helium ions influences the precise depths and locations where the helium ions and their associated energy are deposited [4][5][6]. For magnetic confinement fusion, the implantation of helium into the near surface of tungsten has been shown to lead to the development of a surface nanostructure called tungsten 'fuzz' [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructure growth, which is affected by the location and depth of the implanted helium [4,8] and sputtering by higher energy helium ions [13], has been found to vary with the local grain orientation [4,14,15]. One factor driving this variation is helium ion channeling [4,14], which influences both the implantation of and sputtering by helium.…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate or alleviate the brittle behaviors and satisfy the fusion engineering application, an advanced W material is required and developed. Many researchers claimed that grain boundaries can act as traps to annihilate point defects (interstitial atoms or vacancies) from irradiation [12,[17][18][19][20]. Klimenkov et al [12] and Fukuda et al [17] performed a neutron irradiation test on W materials and found that the neutron Tungsten www.springer.com/42864 irradiation-induced defects were likely to gather or be annihilated at grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Klimenkov et al [12] and Fukuda et al [17] performed a neutron irradiation test on W materials and found that the neutron Tungsten www.springer.com/42864 irradiation-induced defects were likely to gather or be annihilated at grain boundaries. EI-Atwani et al [18][19][20] reported the effects of grain sizes on the irradiation resistance of pure W materials that the grain refinement could enhance its irradiation resistance. Tan et al [21] performed an ELM-like thermal shock test on the second-phase-doped W materials with a report that the addition of the second phase would improve the resistance by strengthening grain boundaries.…”
Section: Introductionmentioning
confidence: 99%